Hypoglossıa: A Case Report - Yahya Tosun; Ali Vehbi Tuncer; Cihangir Özkınay; Şule Tosun (Galenos Yayinevi, 1992)
Hypoglossia-hypodactylia is a congenital malformation in which oro-mandibular anomalies are associated with assymetric reduction of defects of the limbs. In this case report, systemic features of this malformation, hypoglossia and associated orthodontic anomalies were presented.